Christophe Jaffrelot, The Pakistan Paradox: Instability and Resilience - Mr. Sajid Aziz (CISS Insight Journal, 2015)
In first part of the book titled, “Nationalism without a nation-and even without a people?” the author traces the historical roots of the centralizing ideology of Pakistani state in the twilight of Muslim power in mid-nineteenth century in the undivided Indian sub-continent. The seed of Muslim separatism, smithed in the collective psyche of Muslim elite in UP, would bloom into the flower of Aligarh Movement, to Muslim League and its ‘communal ideology.’ Jaffrelot argues state-formation in Pakistan had certain historical streaks and continuum which could possibly be traced back to Pakistan Movement and it ideology. This centralizing ideology, with its foundation on Islam and Urdu, has been a source of considerable resentment among certain ethnic groups and has promoted ‘the poison of provincialism.’ Though he does allude, though sparingly, to the imperative of a unifying force against the threat of a stronger neighbor, which was always reluctant to ‘accept’ the independence of Pakistan.